PENAHANAN DAN PENANGGUHAN PENAHANAN DALAM TEORI DAN PRAKTEK - Thomas Abbon (to-ra, 2018)
Abstract The issue of upholding the rule of law is a chore that must be resolved by the current government. The state and nation have been disadvantaged from all aspects, because in the end the harassment of the law has given rise to corruption, collusion and nepotism. One of the things that stands out about law enforcement is the issue of detention and suspension of detention and sentencing that has to do with detention. The problem of detention and the detention in practice so far has been widely distorted by unscrupulous law enforcers and this institution has become an "open business arena". Detention and suspension of detention is actually a legal effort, which aims to realize the enforcement of the law itself, because detention is only allowed as long as there is suf cient preliminary evidence, and detention is solely in order to facilitate investigation / examination and besides that detention is also intended as protecting the suspect / defendant from violence / other people (eigenrichting). The suspension of detention should be able to be given to every suspect / defendant who provides guarantees according to the law, unless otherwise speci ed in certain cases. In addition there is another side of the Criminal Procedure Code which determines that detention is part of punishment, so it has become a habit in practice that if a suspect / defendant who was originally detained "must be sentenced" .From the facts that are decomposed in the past this has brought a a very dif cult situation to nd out who really deserves detention or suspended detention and it turns out everyone is nally able to pay "anything" to release himself from the snare of detention even though it should not be his right. Keywords: rule of law; corruption, collusion, and nepotism; legal effort.